Role of antioxidants in the pigmentation of ornamental fishes - Yuli, A.; Muhamad, D.C.; Yaya, R.; Dikdik, K. (Iranian Fisheries Research Organization, 2024)
Beyond aesthetics, the varied pigmentation in fish serves as evidence of manifold functions and has ecological importance. Fish pigmentation is an adaptive feature and critical to their survival. Despite their evolved pigmentation for survival and adaptation, fish are not immune to biochemical challenges presented by their surroundings. Harmful free radicals generated by various factors can lead to oxidative stress, impacting cellular components like pigments. Oxidative stress arises from an imbalance between the production of reactive oxygen species and cellular antioxidant defense mechanisms. Nevertheless, antioxidants play a role as crucial protectors, coordinating the defense of cells against oxidative damages. This review aims to elucidate the relationship between antioxidants and fish pigmentation by examining the sources of antioxidants in fish diets and their specific effects on pigmentation. The use of antioxidant compounds offers a promising avenue to mitigate pigmentation loss, enhance carotenoids production, and improve overall fish coloration, contributing to both aesthetic and physiological aspects in the aquaculture industry.